Masticatory muscle tendon-aponeurosis hyperplasia diagnosed as temporomandibular joint disorder: A case report and review of literature. (January 2021) - Elsayed, Nagwan; Shimo, Tsuyoshi; Harada, Fumiya; Takeda, Shigehiro; Hiraki, Daichi; Abiko, Yoshihiro; Nakayama, Eiji; Nagayasu, Hiroki
Highlights: MMTAH is a new clinical entity, misdiagnosed as temporomandibular joint disorder. MMTAH is diagnosed based on a square mandible, cord-like masseter muscle aponeurosis, and limited mouth-opening. Aponeurectomy combined with coronoidectomy is the treatment of choice for a better prognosis. It is important to evaluate the patient's compliance with mouth-opening training before surgery. Abstract: Introduction: Masticatory muscle tendon-aponeurosis hyperplasia (MMTAH) is a new clinical entity that presents mainly with trismus due to hyperplasia of the masseter aponeurosis and temporalis muscle tendon. However, the etiological factors of this disease are unknown; it is often mistreated as temporomandibular joint disorder (TMD). Presentation of case: We report a 32-year-old female patient complaining of bilateral pain in her jaw and difficulty opening her mouth. She was first diagnosed as TMD and treated with a splint; however, her symptoms did not improve. Clinical examination revealed a square mandible, tenderness in the left and right temporalis muscles and masseter muscles, and tenderness along the anterior border of the masseter muscle. Her maximum mouth-opening was 30 mm. Short TI inversion recovery magnetic resonance imaging showed areas of low intensity at the anterior border of the masseter muscle and around the coronoid process where the temporalis muscle tendon attaches. Consequently, the diagnosis made based on the clinical and radiographic findings was MMTAH. Bilateral coronoidectomy was performed, followed by a rehabilitation program for six months. The maximum opening was maintained at 48 mm two years after the operation. Discussion: MMTAH was treated as type 1 TMD until it was recognized as a new disease at the conference for the Japanese Society for Oral and Maxillofacial Surgeons. Since then, many clinicians have become aware of this particular condition, and different treatment modalities have been proposed. Conclusion: Clinicians should consider MMTAH as a differential diagnosis when the patient's chief complaint is gradually decreasing mouth-opening.